The hidden heterogeneity of inflation expectations and its implications - Lena Dräger; Michael Lamla; Damjan Pfajfar (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2020)
Using a new consumer survey dataset, we document a new dimension of heterogeneity in inflation expectations that has implications for consumption and saving decisions as well as monetary policy transmission. We show that German households with the same inflation expectations differently assess whether the level of expected inflation and of nominal interest rates is appropriate or too high/too low. The 'hidden heterogeneity' in expectations stemming from these opinions is related to demographic characteristics and affects current and planned spending in addition to the Euler equation effect of the perceived real interest rate. Furthermore, these differences in opinions affect German households differently depending on whether they are renters or homeowners.
Keywords: E31; E52; E58; D84; 330; Macroeconomic expectations; monetary policy perceptions; survey microdata